IMPLEMENTASI PROGRAM PELAYANAN ADMINISTRASI TERPADU KECAMATAN (PATEN) (STUDI DI KECAMATAN PURWOKERTO UTARA, PURWOKERTO SELATAN, PURWOKERTO TIMUR DAN PURWOKERTO BARAT) - Rais Agil Bahtiar Bahtiar (Department of Public Administration, Faculty of Social and Political Science, Universitas, 2018)
Abstract: This research is about Implementation of Integrated Administrative Service Program of Sub-District (PATEN) in Purwokerto. This research was conducted in four sub-districts in Banyumas District, North Purwokerto Sub-district, South Purwokerto Sub-district, Purwokerto Timur Sub-district and West Purwokerto Sub-district. This research uses explanatory quantitative approach. The policy implementation model used in analyzing the implementation of PATEN is the model proposed by George C. Edward III. This model explains that there are four variables that play a role in achieving successful implementation of communication, resources, disposition and bureaucratic structure. The results showed that the success rate of implementation of PATEN is in the medium category. In general, PATEN has helped to bring the public services to be more accessible, but still has constraints and needs needed to be overcome. One aspect that is needed to be improved is the resources owned by each District Office because it causes the PATEN implementation in each sub-district to not run consistently. While communication, resource, disposition and bureaucratic structure are found to have positive relationship and significant influence on successful implementation of PATEN both individually and collectively.Keywords: Integrated Administrative Service Program of Sub-District, Policy implementation, Public policy